Dexmedetomidine promotes the functional recovery of mice after acute ischemic stroke via activation of the a2-adrenoceptor - Peng, Yuhao; Hu, Xiaoling; He, Haifeng; Zhou, Xinting; Luo, Zhonghui (Folia Neuropathologica, 2024)
Ischemic stroke (IS) is a well-known acute cerebrovascular disease characterized by high disability, morbidity, and recurrence rates with no effective treatments. Dexmedetomidine (DEX), a selective a2-adrenoceptor agonist used in anaesthesiology and pain management, has been found to exhibit neuroprotective effects in various diseases. However, its role in IS and the underlying mechanisms remains to be determined. Hence, the aim of the present study was to investigate the neuroprotective role of DEX in the recovery of mice following middle cerebral artery occlusion (MCAO). Mice were used to establish the animal model, and then DEX was injected. Behavioural tests (neurological function assessments, grip test, and rotarod test), brain water content measurement, ELISA, and measurement of oxidative stress were performed. DEX activated a2-adrenoceptor and resulted in reduced brain injury, as indicated by the decreased brain water content, S100 Calcium Binding Protein B (S100B) content, and neuron-specific enolase (NSE) content, whilst also inhibiting oxidative stress, as indicated by the increased total antioxidant capacity, catalase, glutathione, and superoxide dismutase levels, and decreased malondialdehyde and glutathione oxidized levels. Neuroinflammation was also reduced as indicated by the decrease in IFN-g, IL-1a, IL-1b, IL-6, TNF-a, and MMP levels, improved the recovery of neurological function, as indicated by the decreased neurological function score and mNSS, and increased grip strength and rotarod performance in MCAO mice. These combined results suggest that DEX may be a novel strategy for the treatment of IS.